Pengaruh Lingkungan Keluarga dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa Melalui Self Efficacy Pada Mahaasiswa Jurusan Ilmu Pengetahuan Sosial - Saleh, Muhammad Aditya; Ratumbuysang, Monry Fraick Nicky Gillian; Hasanah, Mahmudah; Harahap, Alfi Fadhilah Hakim (Universitas Negeri Surabaya, 2024)
This study aims to analyze the effect of Family Environment and Entrepreneurship Education on Entrepreneurial Interest through self-efficacy in Students of Social Science Department. The data were collected through observation and questionnaires and analyzed with a quantitative descriptive approach. The subjects in this study were students majoring in Social Sciences. The population used in this study amounted to 847 respondents, with a sample of 271 respondents. The analytical tool used is Structural Equation Modeling (SEM) using SmartPLS version 3.0 software. The results showed that there is a significant influence directly between the family environment, entrepreneurship education, and self-efficacy on entrepreneurial interest of students majoring in social science FKIP ULM. And there is an indirect influence between the family environment and entrepreneurship education on the entrepreneurial interest of students majoring in social science FKIP ULM through self efficacy as an intervening variable.